Impact exercises absolute power and relative to the lower muscles of the parties to develop some physical and mechanical capacity in Almway Tai - mseer, Ali (Journal of Physical Education, 2012)
Almway Tai like other sports, the level of technical performance depends which of the various movements and basic skills on the amounts of power that can be produced by the muscles in sports. When we speak of the strengths of the player Almway Tai, you should Nnsabha always to body weight, which is defined by force of muscle relative, which means the amount of power that belongs to all (1) kg and one of the force the muscle to the body part when dealing against body weight and expressed by the relationship ( maximum power to the body part / body weight) as long as the player in this game corresponds to a discount in the same talents. On the other hand can we talk about the absolute power of these muscles when the work at all (against an external force is body weight) and that have a relationship between the force optimum for these muscles and sectional physiological, and both types can be designed training programs according to the type of force required, (relative and absolute) The researcher seeks to clarify the importance of studying these two forces through the design of training programs for each type and extent of the effect of each important part in some of the offensive skill players Almway Tai and the level of physical variables. The researcher used the tools, equipment and means used in the research were identified physical attributes after having heard the most important sources, references and studies of the science of sports training and tests and measurements have been identified (explosive power of the muscles of the feet - the explosive power of the muscles of the legs - force deals as soon as the muscles of the two men) were identified test the long jump of Persistence and three Hjlat every man. , The performance skills evolved to include the measurement of the angular velocity of the hip joint and the peripheral speed to it. The effect appeared evident in the development of muscle groups working in the tidal movements and bending the joints related to these movements by the exercises used for absolute and relative power. And the emergence of Ttorvi (strength characterized as fast, and explosive power) as well as the evolution of the angular velocity and peripheral to the man striking. Demonstrating the effectiveness of the exercises used in the training curriculum sample